(untitled) (World Bulletin of Public Health, 2024)
Among the main factors causing metabolic disorders in the body, we can highlight insufficient physical activity, unbalanced nutrition, hormonal predisposition. Various acute and chronic diseases also affect human metabolism. Metabolics are drugs that correct metabolism and vital energy in the body, help speed up metabolism